(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Medial prefrontal cortex (mPFC) is considered to be involved in human cognition to mPFCin terms of learning and memory. Hypoxia is one of the crucial factors causing secondary damage incerebral hemorrhage and traumatic brain injury. However, the underlying mechanisms and possibletherapeutic approach to prevent neuronal damage has not been attempted yet. Therefore, the present studyaimed to investigate the role of Tualang honey on medial prefrontal cortical neuronal morphology andcholinergic markers such as acetylcholine (ACh) and acetylcholinesterase (AChE) following exposure to normobaric hypoxia in rats. Material and methods: Adult male Sprague-Dawley rats were dividedinto four groups: (i) sucrose treated non-hypoxia, (ii) sucrose treated hypoxia, (iii) Tualang honeytreated non-hypoxia and (iv)Tualang honey treated hypoxia. Rats received sucrose (1 mL of 7.9%) andTualang honey (0.2 g/kg), respectively, for 2 weeks prior to hypoxia exposure. Morphological study wasperformed by using Nissl staining and cholinergic markers were estimated by ELISA technique. Resultsand discussion: Sucrose treated hypoxia group showed significantly lower mean ACh and higher meanAChE concentrations (P<0.05) compared to sucrose and honey treated non-hypoxia groups. Interestingly,mean ACh concentration was significantly increased and mean AChE concentration was significantlydecreased in Tualang honey treated hypoxic rats compared to sucrose treated hypoxic rats. Morphologicaldata showed that hypoxia caused neuronal damage in mPFC in sucrose treated hypoxia group whereasTualang honey treated hypoxia group significantly prevent neuronal damage. Conclusion: Tualang honeyprotects hypoxia-induced mPFC neuronal damage through improvement of the brain cholinergic markersin male rats exposed to normobaric hypoxia. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.122-129